A Decomposition Analysis of CO2 Emissions in the United States - Vinuya, Ferdinand; DiFurio, Ferdinand; Sandoval, Erica (2012)
This article decomposes the growth in US CO2 emissions by state. Using the Logarithmic Mean Divisia Index (LMDI) method, we account for CO2 emissions change in each state between 1990 and 2004. The change is decomposed into five effects: (a) emissions per unit of fossil fuel; (b) share of fossil fuel in total energy consumption; (c) energy intensity; (d) gross state product per capita; and (e) population. Results show that for the past 15 years gains in the efficiency of energy use in the economy, the lowering share of fossil fuels in total energy consumption and lowering of emissions intensity of fuels all contributed to offsetting the effect of gross domestic product (GDP) per capita and the population growth in carbon emission across the US.